Libyan Tourism and Rescuing Strategy (Importance of Image) (Global Journal of Management and Business Research, 2013)
The tourism industry is one of the most important industries in the world since it employs â€œmore than 250 million people worldwideâ€ (Coshall 2003, p.4). This industry, which includes transport, lodging, and catering, is expected to generate $12,119 billion of revenues and 279,346,000 jobs in 2016 (Asia-Pacific Economic Cooperation, 2006). The tourism industry worldwide is also expected to indirectly and directly contribute 10.9% to Gross Domestic Product (Asia-Pacific Economic Cooperation, 2006). However, the tourism industry is an extremely sensitive and vulnerable activity which can be impacted by important events such as terrorism, political insecurity, and natural disasters (Coshall, 2003).
Keywords: Libyan Revolution; Libyan uprising; political situation; Social situation; successful tourism